Effects of synchrotron‐based X‐rays and gold nanoparticles on normal and cancer cell morphology and migration. (13th January 2023) - Shahhoseini, Elham; Nakayama, Masao; Panettieri, Vanessa; Hall, Chris; Feltis, Bryce; Geso, Moshi
Abstract : The effects of synchrotron‐based kilovoltage X‐rays on a cell's morphology and motility are investigated. Abstract : It has been shown lately that gold nanoparticles (AuNPs) and ionizing radiation (IR) have inhibitory effects on cancer cell migration while having promoting effects on normal cells' motility. Also, IR increases cancer cell adhesion with no significant effects on normal cells. In this study, synchrotron‐based microbeam radiation therapy, as a novel pre‐clinical radiotherapy protocol, is employed to investigate the effects of AuNPs on cell migration. Experiments were conducted utilizing synchrotron X‐rays to investigate cancer and normal cell morphology and migration behaviour when they are exposed to synchrotron broad beams (SBB) and synchrotron microbeams (SMB). This in vitro study was conducted in two phases. In phase I two cancer cell lines – human prostate (DU145) and human lung (A549) – were exposed to various doses of SBB and SMB. Based on the phase I results, in phase II two normal cell lines were studied: human epidermal melanocytes (HEM) and human primary colon epithelial (CCD841), along with their respective cancerous counterparts, human primary melanoma (MM418‐C1) and human colorectal adenocarcinoma (SW48). The results show that radiation‐induced damage in cells' morphology becomes visible with SBB at doses greater than 50 Gy, and incorporating AuNPs increases this effect. Interestly, under the same conditions, no visible morphological changes were observed in the normal cell lines post‐irradiation (HEM and CCD841). This can be attributed to the differences in cell metabolic and reactive oxygen species levels between normal and cancer cells. The outcome of this study highlights future applications of synchrotron‐based radiotherapy, where it is possible to deliver extremely high doses to cancer tissues whilst preserving surrounding normal tissues from radiation‐induced damage.